Impact of Cognitive and Metacognitive Strategies Practices on EFL Achievements among Saudi EFL Learner in Public Sector University, Abha, Kingdom of Saudi Arabia - Akram, Hira Tauseef (International Journal of English Literature and Social Sciences (IJELS), 2019)
Language learning strategies have played pivotal role in students’ language learning in the context of English as a foreign language. This study determines the impact of Cognitive and metacognitive learning strategies practices on EFL achievements among Saudi EFL learners. Cross sectional study has been conducted among Saudi Arabian students in public sector university, Abha, from Oct’2018 to March 2019. Random sampling technique used to target 323 students. Data were collected via self administered questionnaire, which includes; Demographic variables, six dimensions of cognitive and metacognitive strategies, and Students EFL scores. SPSS-23 Version used to analyze data. Qualitative and Quantitative variables explored via frequency & percentage and mean±SD respectively. Pearson correlation used to assess relationship between cognitive and metacognitive strategies and EFL achievements. Multiple regression has used to assess the effects of cognitive and metacognitive strategies on EFL Achievements. Response rate was 80.5%. Out of 323, 260 duly filled questionnaires were received. Most of the students were females (58.8 %), age group between 15-19years (58.5%), and belong to sophomore class (45.8%). Findings of the study revealed, cognitive and metacognitive strategies positively correlated with EFL Achievements at P-Value <0.05 & < 0.01 and use of cognitive and metacognitive strategies explained significant amount of variance in Grammar, vocabulary, Reading, Listening, Writing and EFL final exam scores. This study provides insight to include language learning strategies in university pedagogy and train teachers to facilitate students to utilized language learning strategies.